Porous CuWO4/WO3 composite films with improved electrochromic properties prepared by sparking method - Winai Thongpan (2020)
© 2019 The porous CuWO4/WO3 composite films with various atomic ratios have been fabricated on indium-doped tin oxide glass substrates by sparking method. The structural, morphological, optical, and electrochromic properties of samples have been investigated. The SEM image revealed porosity morphology of deposited films which is highlight of the sparking method. The CuWO4/WO3 composite in monoclinic structure were confirmed by XRD, Raman spectroscopy, and XPS. Compared with pure WO3 film, CuWO4/WO3 composite film at Cu/W atomic ratios of 0.29 shows improved coloration efficiency from 49.6 to 74.4 cm2/C which confirmed by cyclic voltammetry. Moreover, fast switching speeds of 1.9 s and 1.6 s for the coloration and bleaching state were observed for the film containing this ratio.